How does income inequality influence international migration? - Thomas Liebig; Alfonso Sousa-Poza (European Regional Science Association (ERSA), 2003)
The increasing importance of highly-skilled migration in times of so-called 'skills shortages' is leading to a growing interest in the determinants and characteristics of highly-skilled migration. However, migration theory with regard to the highly-skilled is not well developed. An important strand of literature that clearly serves for the derivation of empirically testable hypotheses about the determinants of particular types of migrants is self-selection theory. This theory dates back to Roy (1951) and has been adopted by Borjas (1987) for the analysis of the relation between the income distribution and the skills of migrants. He concludes that a relatively more equal income distribution in the host country vis-à-vis the source country leads to a negative self-selection of migrants (i.e. the lowly-skilled will be particularly attracted) and vice versa. Borjas has confirmed this hypothesis with data on immigration to the US. Chiswick (1999) and others, however, have questioned these results. Sample-selection biases may arise in single-country analyses and in all studies based on host-country data, due to the impact of host-country specifics such as migration policy, network migration, and the like. Due to a lack of internationally comparable data, however, international empirical studies with data from the origin countries have not been undertaken to resolve the dispute between Borjas and Chiswick. Furthermore, data on the intentions to emigrate (as opposed to actual migration data) has the distinct advantage of being free from the above-mentioned selection-bias problem. This paper sheds some new light on the self-selection controversy by analysing the relationship between country-specific emigration propensities and each country's score on the Gini-Index on inequality. The 1995 International Social Survey Programme (ISSP) conducted a survey on national identity, which gathers the necessary data in a rich international microdata set. We run probit-regressions with two samples, one including all surveyed persons and one including only the sub-sample of the highly-skilled. By relying on the Gini index as a proxy for wage inequality, the paper follows Borjas' (1987) approach. Borjas, however, proxies skills differentials by income differentials. Chiswick (1999) argues that these two differentials may only be poorly related. The analysis presented here partly avoids this criticism, as we compare the sub-sample of highly-skilled persons with all surveyed individuals and with the medium- and lowly-skilled. A strong positive correlation between skills and income, as predicted by standard economic theory, therefore suffices for the validity of our approach. The main result of this paper is that, ceteris paribus, a more egalitarian income distribution is associated with lower emigration propensities, while income inequality does not have any impact on the emigration propensities of particularly highly-skilled persons. These results seem to contradict Borjas' prediction that the highly-skilled should be particularly attracted by countries which have relatively high returns to skills. Thus, our analysis is more in line with the arguments put forward by Chiswick (1999) and others.
Keywords: 330